Mapping kewajiban Guru Bimbingan dan Konseling dalam Peraturan Permendikbudristek No. 25 Tahun 2024 - Ridwan Lubis; Neviyarni Neviyarni; Yarmis Syukur (Universitas Negeri Padang, 2025)
This study aims to systematically map the obligations of guidance and counseling teachers (BK teachers/counselors) in the Regulation of the Minister of Education, Culture, Research, and Technology Number 25 of 2024 and analyze the implications of the changes to the practice of providing guidance and counseling in educational units. By using a normative legal approach (statute approach and conceptual approach) as well as content analysis and norm mapping techniques, this study identifies five core provisions that form the new basis for calculating the workload of BK teachers, namely: (1) the core obligation to serve a minimum of 5 study groups per year (Article 4 paragraph 4), (2) the equivalence of additional heavy tasks equivalent to 3 classes (Article 5 paragraph 1), (3) the equivalence of additional light tasks (?2 tasks) equivalent to 1 class (Article 6 paragraph 5), (4) a minimum limit of 4 classes for BK teachers with other additional tasks (Article 6 paragraph 7), and (5) exceptions for educational units with classes